Efektivitas Teknik Sosiodrama Dalam Layanan Bimbingan Kelompok Untuk Meningkatkan Penyesuaian Diri Siswa - Dina Maulina; Suhertina Suhertina (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
This research aimed at knowing the effectiveness of Sociodrama technique on group guidance service in increasing student self-adjustment at State Senior High School 2 Singingi District, Kuantan Singingi Regency.  It was a pre-experimental research with one group pretest and posttest design.  The subjects of this research were the tenth-grade students, and the object was Sociodrama technique on group guidance service in increasing student self-adjustment.  All the tenth-grade students of MIPA 1 that were 30 students were the population of this research.  Purposive sampling technique was used in this research, and 10 students having low self-adjustment were selected as the samples.  Questionnaire, documentation, and observation were the techniques of collecting the data.  The technique of analyzing the data was signed-rank test or Wilcoxon test. The research findings showed that student self-adjustment before the action (pretest) was on medium category and the mean total score was 46.1.  It increased after being given the treatment (posttest) using Sociodrama technique on group guidance service, the increase was 15.7, so the mean total score was 61.8 and it was on high category.  Based on the result of testing the hypothesis using Wilcoxon test, it was obtained the probability score 0.005 that was lower than 0.05.  It meant that Null hypothesis (H0) was rejected and Alternative hypothesis (Ha) was accepted.  It could be concluded that Sociodrama technique on group guidance service was effective in increasing student self-adjustment.